Young Afro-Costa Rican voices waiting an awakening - Barrett-Parkinson, Shalaisha (2022)
This essay offers a walk through the events of Afro-Costa Rican culture, to present motivations and challenge the young Afro-Costa Rican generation and induce an awakening of their literary voice.